THE CONTRACT CHANGE ORDER ANLYSIS OF BRIDGE CONTRUSTION EMPLOYEES OF BIG HALL PROJECTS IMPLEMENTATION OF NATIONAL ROAD WHICH INFLUENCES THE TIME PERFORMANCE - Dwi Aneka Kartini; Ghina Rizqandi Q.A (Journal of Industrial Engineering & Management Research, 2024)
There is always problem of change order during the implementation of the project, either in first, middle, or the last project which involves the service user and the service provider. In every construction projects, there is always changing which called as change order (Jaydeep, et al, 2015). The change order could directly increase the cost of the project because of the additional material and volume, conflict of implementation schedule, rework, increase the overhead and increase the employees’ fee (Hanna, et al, 1999). The aim of this research is to find the causative factors of change order and identify the dominant factors which cause the change order which influences the time performance of the national bridge project. The data collecting technique of this research used survey and the previous research. The analysis method that was used to find the dominant factors was Partial Least Square (PLS). There are 28 dominant factors the cause of change order which influences the time performance on national road project. From the 28 dominant factors, they will divide in to 3 factor groups.